Ownership Structure And Firm Value: The Mediating Role Of Financial Performance - Wijayanti, Mita Meilina; Shodiq, Muhammad Ja'far (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study examines the direct and indirect effects of institutional ownership and managerial ownership on firm value, with financial performance as a mediating variable. Methodology: The study utilizes secondary data from 155 manufacturing firms listed on the Indonesia Stock Exchange (IDX) for the 2020–2023 period. A purposive sampling technique is used, and data are analyzed using SPSS 26 with regression and path analysis. Findings: Institutional ownership negatively affects firm value and positively affects financial performance. Managerial ownership positively influences firm value but does not affect financial performance. Financial performance positively influences firm value. Results: Financial performance mediates the relationship between institutional ownership and firm value but does not mediate the relationship between managerial ownership and firm value. Novelty: This study extends existing literature by testing the mediating effect of financial performance using recent post-pandemic data. Originality: The research uniquely contributes by combining ownership structure variables with financial mediation in an emerging market context. Conclusions: Institutional monitoring increases financial performance but may negatively signal firm value. Managerial ownership improves firm value directly but lacks effect on profitability. Type of Paper: Empirical research paper.